THE EFFECT OF THE DRUG MUMIJO ON THE PARAMETERS OF PLATELETS IN RESIDENTS OF AREAS WITH A CONSTANT COMBINED EFFECT OF NATURAL AND TECHNOGENIC IONIZING RADIATION - P.G. Kovalenko (Проблеми екології та медицини, 2023)
Peripheral blood platelet parameters were studied in 53 apparently healthy female volunteers living in the city of Kropyvnytskyi, Kirovohrad region. 2 groups were formed: the main group received the biologically active supplement (BAD) mumijo once a day for 30 days, and the control group did not receive this drug. The content of platelets in the blood (PLT), the mean platelet volume (MPV), the relative width of the distribution of platelets by volume, i.e. the platelet heterogeneity index (PDW), and plateletcrit – fraction (%) of the volume of whole blood occupied by platelets (PCT), were studied before and after the course of the BAD mumijo. The results of the study showed a positive effect of the BAD mumijo on platelet parameters. Thus, the frequency of detection of persons with a reduced platelet content probably (Р<0.05) decreased, the limits of individual fluctuations of the platelet content shifted upwards to the limits of the norm, the average indicators probably increased (Р<0.05) with a tendency towards normalization. Indicators of plateletcrit, which reflects the fraction (%) of the volume of whole blood, made up of platelets, the average volume of platelets reliably (Р<0.05) increased to the average indicators of the norm. The limits of individual variations in the width of the distribution of platelets shifted to the normalization of the indicator. Changes in platelet parameters indicated an increase in their content due to the proportion of young and more functionally capable platelets. It has been established that the BAD mumijo is an effective radiomodifier of the effect of constant combined exposure to natural and technogenic man-made low-intensity ionizing radiation. The obtained results of the research can be useful and have a perspective for wider application in regions similar to the Kirovohrad region and the city of Kropyvnytskyi.